The Assignment of Risk Mitigation Tasks Based on The RACI Matrix and Key Risk Indicator - Hartono, Yudi; Cahyo, Winda Nur; Immawan, Taufiq (Jurnal Ilmiah Teknik Industri, 2024)
Risk management can be applied to process risks in the organization by identifying, mitigating and monitoring risks. Risk management activities cannot be executed without the participation of risk owners. Risk owners are the main key to the successful implementation of risk management. Therefore, risk management suppose to be well distributed to risk owners. Te Aming x Auntie has carried out risk calculations and evaluations using risk houses and key risk indicators, it is known that the risk agents who are the source of problems in Te Aming x Auntie operations are employees who didn’t carry out inspections and didn’t have supervision. Based on these calculations, risk mitigation activities are accomplished which include activities to increase supervision, implement rewards and punishments, and assess employee performance. To ensure risk mitigation activities are carried out well, a RACI matrix is created to organize and distribute risk management activities to all related parties.